Structural and Functional Changes in Supraspinatus Tendinopathy through Percutaneous Electrolysis, Percutaneous Peripheral Nerve Stimulation and Eccentric Exercise Combined Therapy: A Single-Blinded Randomized Clinical Trial. - Góngora-Rodríguez, Jorge; Rosety-Rodríguez, Miguel Ángel; Rodríguez-Almagro, Daniel; Martín-Valero, Rocío; Góngora-Rodríguez, Pablo; Rodríguez-Huguet, Manuel (MDPI, 2024)
Shoulder tendinopathies produce pain and reduce functionality. The aim of this randomized clinical trial was to analyze the effects of Percutaneous electrolysis (PE), Percutaneous peripheral Nerve Stimulation (PNS) and eccentric exercise (EE) on pain (NPRS), strength, electromyographic activity, ultrasound characteristics of the tendon (echogenicity, thickness and hypervascularization) and functionality (DASH and SPADI) in individuals with supraspinatus tendinopathy. Participants (n = 50) were divided into two groups; they received 4 treatment sessions, 1 per week, of PE and PNS (n = 25) or 10 treatment sessions of TENS and US (n = 25). Both groups performed the EE program consisting of 3 sets of 10 repetitions of each of the 3 exercises, twice a day, during the 4 weeks. Follow-up was carried out at 4, 12 and 24 weeks after the start of the intervention. There are statistically significant differences in the analysis between groups (p < 0.001) in the post-treatment and follow-up measurements favorable to the PE+PNS+EE treatment on pain (NPRS), strength, supraspinatus electromyographic amplitude, ultrasound characteristics of the tendon (echogenicity, thickness and hypervascularization) and DASH and SPADI questionnaires. The combined treatment with PE, PNS and EE is an effective option in the clinical management of tendinopathies, with positive results in the short and long term on the variables studied.
Keywords: Hombro doloroso - Ejercicios terapéuticos; Percutaneous electrolysis; Peripheral nerve stimulation; Physical therapy; Shoulder pain; Supraspinatus tendinopathy; Ultrasonography